2015
DOI: 10.1097/aog.0000000000000708
|View full text |Cite
|
Sign up to set email alerts
|

Association of Health Literacy With Adherence to Screening Mammography Guidelines

Abstract: Of all the sociodemographic variables examined, health literacy had the strongest relationship with use of screening mammography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 24 publications
1
47
1
Order By: Relevance
“…Financial barriers include direct costs of screening, and non-medical out of pocket costs associated with screening participation. While cost is often significant barrier to participation in screening elsewhere [20,21,22], direct costs are not a barrier to screening for Australian women given that the Australian program is free of charge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial barriers include direct costs of screening, and non-medical out of pocket costs associated with screening participation. While cost is often significant barrier to participation in screening elsewhere [20,21,22], direct costs are not a barrier to screening for Australian women given that the Australian program is free of charge.…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy includes the capacity to communicate, assert, and enact these decisions. Previous breast screening research that explored health literacy focused on reading, writing, and numeracy skills related to comprehension of health information (known as functional health literacy) and identified associations with non-participation in breast screening [21,25,26]. Individuals with low functional health literacy were more likely to hold fatalistic cancer attitudes, less likely to identify the purpose of cancer screening procedures, and less inclined to engage with information about health conditions that they do not have [27].…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38] In recent years, studies have also identified significant shortcomings in the delivery of preventative care to patients with IBD, particularly with respect to vaccination. 39 Lower rates of vaccination among IBD patients have been linked to poor patient awareness, patient concerns about adverse effects, gastroenterologist knowledge deficits and health care system challenges, such as time constraints and poor communication with primary care providers.…”
Section: Health Maintenance and Preventative Carementioning
confidence: 99%
“…Our findings were also consistent with previous studies, which found lower rates of cancer screening among women who have low income, currently smoke, and are uninsured. 27 Even though no association was seen between social media use and mammogram rates, social media holds potential for health support, intervention and promotion campaigns. For example, Attai et al found that participation in a breast cancer Twitter TM support group increased patient knowledge regarding the disease condition and management and significantly decreased anxiety levels.…”
Section: Content Analyses Of Breast Cancer Specific Facebook Groupsmentioning
confidence: 99%